2020
DOI: 10.1002/slct.202000136
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Addition of Unactivated Ketones with β‐Nitrostyrenes Mediated by Bifunctional L‐Prolinamide Organocatalysts

Abstract: The catalytic activity of two types of L‐prolinamide organocatalysts was investigated for asymmetric Michael addition reaction of cyclic/acyclic ketones with β‐nitrostyrens. L‐Prolinamides bearing amino groups on phenyl ring worked well, though their catalytic efficiency as well as selectivity was found to be dependent upon the position of amine group to the amide bond. Organocatalyst having –NH2 group ortho to amide bond provided the best results. Substrate scope was also studied by performing the reaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Despite many striking features, organocatalysts are seldom used in industry because of their high catalyst loading, difficulty in separation, nonrecyclability and so forth. Even for the reduction of global chemical waste, these factors are imperative and need to be addressed rigorously. However, catalyst immobilization can be marked as an efficient technology to produce easily separable, reusable, and aqueous catalytic systems with a high level of stereoselectivity …”
Section: Introductionmentioning
confidence: 99%
“…Despite many striking features, organocatalysts are seldom used in industry because of their high catalyst loading, difficulty in separation, nonrecyclability and so forth. Even for the reduction of global chemical waste, these factors are imperative and need to be addressed rigorously. However, catalyst immobilization can be marked as an efficient technology to produce easily separable, reusable, and aqueous catalytic systems with a high level of stereoselectivity …”
Section: Introductionmentioning
confidence: 99%
“…The electrondonating groups on nitroolefins 83 directed moderate ee whereas electron-withdrawing substituents offered increased ee of the product 84 (Scheme 21). [68] A novel strategy was developed by Deok-Chan Ha et al in 2020 for asymmetric Michael additions of aromatic ketones 86 to trans-β-nitroalkenes 87 under neutral conditions to provide 88 by using (R,R)-1,2-diphenyl ethylene diamine thiourea catalyst 89. According to the mechanistic pathway, enamine was formed by the reaction of ketone and primary amine thiourea catalyst, which forms double hydrogen bonding with the oxygen of nitroolefin.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies suggested carrying out the reaction at 0 °C; 23,24 however, the attempt was unsuccessful (Table 1, entries 2 and 3). Due to the negative results, we replaced sodium hydroxide with ammonium acetate in glacial acetic acid; 25 unfortunately, the yield did not improve (entry 4, 15%). The protocols consulted at this point used nitromethane instead of nitroethane to perform the Henry reaction; so we hypothesized that the poor yield was due to the inductive effect promoted by the methyl group of nitroethane, thus reducing the acidity of the hydrogen atom.…”
Section: Chemistrymentioning
confidence: 99%